Determinan Tingkat Kemiskinan Di Provinsi Sumatera Utara - Sajida Miftah; Arsita Arsita; Farah Rizkidina; Asnidar Asnidar; Ahmad Ridha (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
North Sumatra Province consists of 25 districts, 8 cities, 325 sub-districts and 5456 sub-districts/villages. The poverty rate is still high in several districts, which in 2006-2022 still have poverty rates above the average poverty rate. Poverty is a serious problem because it is related to human welfare. Therefore, further research is needed regarding the factors that influence poverty. The aim of this research is to determine the effect of economic growth, unemployment, the Human Development Index and the Gini index on poverty levels in the province of North Sumatra. This data analysis uses secondary data via the Central Statistics Agency website with the help of Eviews 12 in 25 districts of North Sumatra province in 2006-2022. The data analysis technique in this research uses multiple linear regression analysis